Basic grammar in use (Cambridge University Press, 2002)
Basic Grammar in Use Without answers, with Audio CD: Reference and Practice for Students of English. The second edition contains new units, more exercises, and a free Audio CD with recordings of example sentences so students can hear the grammar structures they are learning. Each of the 116 units in the Student's Book is presented in a two-page spread, with simple, clear explanations on the left-hand page and practice exercises to check understanding on the right.